Effectiveness of a Promotores Network to Improve Health in an Emerging Latino Community. (June 2022) - Taverno Ross, Sharon E.; Liang, Hai-Wei; Cheng, Jessica; Fox, Andrea; Documet, Patricia I.
Background: Latinos living in emerging communities (i.e., nontraditional destinations with a small but growing population) face obstacles to their mental and physical health. This study evaluated the effectiveness of a 6-month, promotor -led intervention on access to care, physical activity, dietary practices, and perceived social support among Latino adults living in an emerging community, compared with a nonrandomly assigned control group. Method: Participants ( n = 81 intervention; n = 86 control) were drawn from Allegheny county, Pennsylvania. Promotores used an intervention tool offering nondirective social support to assist participants in developing SMART goals to address their life concerns in eight domains (e.g., social, diet, and exercise/recreation); the control group received printed materials. Participants completed a survey in Spanish at baseline and follow-up to assess outcomes and had their height and weight measured. Adjusted linear mixed effects models compared change in outcomes over time. Results: There was a marginally significant improvement in dietary practices in the intervention group at follow-up, and no change in access to care. Both groups experienced an improvement in social support. There was a significant intervention-by-time interaction such that the intervention group increased physical activity by 259 minutes/week compared with the control group. Conclusion: This study demonstrates the potential effectiveness of a promotores network in assisting individuals living in an emerging Latino community to address their life concerns and improve health behaviors. Future studies should include objective and more rigorous measures with a larger sample to replicate these results.